Film Aquaman Sebagai Media Kampanye Kesadaran Lingkungan Global - Karlinda Dewi Anggraini; Andina Mustika Ayu (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2023)
Today environmental issues have grown into quite significant issues. One of the environmental problems that is currently in the spotlight is the marine environment. The sea is one of the 17 goals of the Sustainable Development Goals (SDGs), namely SDG 14 because the sea is an important aspect for the life of living things on earth. marine ecosystem with environmental awareness efforts through the Aquaman film campaign. This research is a type of narrative analysis research, in which the author analyzes any messages contained in the Aquaman film using Ferdinand De Saussure's semiotic analysis technique in an effort to protect the marine environment, in which the messages are packaged in story form. The data collection technique used will use a qualitative method, in which the writer will use a lot of observation persistence as data validity to find features in the Aquaman film that are relevant to the communication campaign process. The result is, this film is used to campaign environmental awareness with 6 messages: (1) Ecological Disunity; (2) Human population control; (3) Comprehensive literacy for the international community; (4) Disaster mitigation by changing behavior; (5) Economic advantage; and (6) Potential conflict